Comparison of nerve graft integration after segmentar resection versus epineural burying in crushed rat sciatic nerves - Cunha,Marco Túlio Rodrigues da (1997)
The aim of the present paper is to compare and correlate the take of nerve segments in a severely crushed nerve. Forty adult Wistar rats had their right sciatic nerve by a "Péan-Murphy" forceps for 40 minutes. In Group 1 (n=20), a segmentar serection in the crushed sciatic nerve was made. A sural nerve segment from the opposite hindpaw was placed in the gap. In Group 2 (n=20), a lontudinal insision in the epineurium of the lesioned sciatic nerve was made. A sural nerve segment was buried underneath the epineurium. The crushed sciatic nerves undergone Wallerian degeneration and endoneurial fibrosis. Sciatic nerves from Group 2 had significant better histological aspects than those from Group 1. Sural nerve grafts presented better degrees of regeneration than crushed sciatic nerves. Sural nerve grafts from Group 2 (burying method) integrated as well as those from Group 1 (segmentar resection).